2013
DOI: 10.1186/1757-2215-6-70
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic pregnancy after transfer of a “euploid” blastocyst screened by DNA microarray

Abstract: BackgroundHigh proportions of human embryos produced by in vitro fertilization are aneuploidy and mosaic. DNA microarray is one of the most practical screening methods to select euploid embryos for transfer. However, mosaic pregnancy is still possible due to embryonic mosacism. Here we report a successful pregnancy after transfer of a mosaic blastocyst with euploid inner cell mass.MethodsA woman with a previous trisomy 13 pregnancy pursued infertility treatment with preimplantation genetic screening by a troph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…It has been found that in about 2 % of pregnancies, the fetus had normal chromosomes while the placenta had either a combination of normal and abnormal chromosomes or totally abnormal chromosomes [14][15][16][17]. Fetal/placental mosaicism is one type of potential mosaicism.…”
Section: Mosaicismmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been found that in about 2 % of pregnancies, the fetus had normal chromosomes while the placenta had either a combination of normal and abnormal chromosomes or totally abnormal chromosomes [14][15][16][17]. Fetal/placental mosaicism is one type of potential mosaicism.…”
Section: Mosaicismmentioning
confidence: 99%
“…Such results may be due to either decreased mosaicism within TE and ICM cells at the blastocyst stage or to an increased likelihood that the ICM is euploid if the mosaic TE contains some euploid cells [18]. Some fetuses with normal chromosomes have a fully abnormal or mosaic chromosome complement within the placenta [15,16]. It has been estimated that approximately 2 % of viable pregnancies are affected by this type of mosaicism, termed Bconfined placental mosaicism^ [16].…”
Section: Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…The examination of individual cells at the blastocyst stage is particularly important to gain insight into possible origins and mechanisms of mosaicism, such as non-disjunction, endoreduplication, anaphase lagging, uniparental disomy, and their prevalence during preimplantation development [Taylor et al, 2014a]. Indeed, mosaicism could be responsible both for false negative and false positive preimplantation genetic screening (PGS) diagnoses [Haddad et al, 2013;Wener et al, 2014].…”
mentioning
confidence: 99%